2009
DOI: 10.1289/ehp.0800114
|View full text |Cite
|
Sign up to set email alerts
|

Preparing for Climate Change: A Perspective from Local Public Health Officers in California

Abstract: BackgroundThe most recent scientific findings show that even with significant emission reductions, some amount of climate change is likely inevitable. The magnitude of the climate changes will depend on future emissions and climate sensitivity. These changes will have local impacts, and a significant share of coping with these changes will fall on local governmental agencies. Public health is no exception, because local public health agencies are crucial providers of disease prevention, health care, and emerge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
51
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 23 publications
(35 reference statements)
5
51
0
2
Order By: Relevance
“…Previous studies of this kind have been undertaken mainly in developed countries including the USA [11,12,15,17,18], Australia [19,20], and Canada [12,13]. Such studies can provide important information to policy makers and assist in developing and promoting practical adaptation measures.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies of this kind have been undertaken mainly in developed countries including the USA [11,12,15,17,18], Australia [19,20], and Canada [12,13]. Such studies can provide important information to policy makers and assist in developing and promoting practical adaptation measures.…”
Section: Discussionmentioning
confidence: 99%
“…The survey focused on topics discussed in the 2006 statewide assessment of the public health impacts of climate change in California, with the exception of wildfires (Drechsler et al 2006). In addition, several health threats that were not included in the survey are likely to be important for California under a changing climate, including drought, wildfire (as mentioned above), and displacement associated with floods and other extreme events (for more detail on the survey, see Bedsworth 2008;2009).…”
Section: Survey Methodologymentioning
confidence: 99%
“…The only other example of regional analysis of climate change preparedness 7 known to the authors found similar patterns of insufficient funding and political support for local adaption planning. In that California-based study, Bedsworth concluded that LHDs in may be better prepared to initiate adaptation planning than department officials perceive through building on existing program areas, echoing a key recommendation from the ClimAID Public Health Sector for New York State.…”
Section: Discussionmentioning
confidence: 64%
“…6 Thus, strategies that specifically address local climate hazards in conjunction with vulnerability factors are critical for preventing negative health outcomes and local public health officials are key foci for adaptation planning. 79 …”
Section: Introductionmentioning
confidence: 99%